Luxury, Lies and Marketing Shattering the Illusions of the Luxury Brand - Sicard, M.; SpringerLink (Online service) (London : Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2013)
Uncovers the truth about luxury brand marketing and shows that like any other commercial brand, they manipulate and influence their customers with traditional commercial techniques. Full of case studies and practical tools for understanding luxury brand marketing the author provides frameworks to help companies with their own branding strategy.
Keywords: Marketing; Leadership; International business enterprises; Behavioral economics; Marketing; Business Strategy/Leadership.; International Business; Behavioral/Experimental Economics